Prevalence of hypertension in mid adolescents in central India: A school based comparative study - Sharma, Roop; Mandliya, Jagdish; Dhaneria, Mamta; Tiwari, H.L (International Journal of Medical Research and Review, 2015)
Introduction: Hypertension among children and adolescents has increased significantly in the developed countries during the past two decades and similar trends are being observed even in the developing world. Methods: Mid adolescent boys and girls (14-16years) of three government and four private schools of Ujjain city were included with sample size of 1000. A pre designed questionnaire regarding nutritional and dietary history was prepared with measurement of anthropometry. Results: The overall prevalence of pre-hypertension and hypertension children in our study is 6.8% and 8.2% respectively, where as worldwide prevalence of hypertension is 7% to 19%. The prevalence of systolic pre-hypertension and systolic hypertension in children of government schools (14-16 yrs) was 7.5% and 8.5% respectively. In private schools out of 75 hypertensive students 49 (65.3%) (p=0.06) were consuming excess calorie. The incidence of systolic hypertension was low in the students with physical, activity ≥1hr/day and it was observed that both TV watching and Computer use were not associated with hypertension. Conclusion: The prevalence of systolic hypertension in boys was higher in private schools as compared to government (7.8%>5.9%). Girls were more hypertensive in government as compared to private schools (12.4%>7.9%). Various factors which were found to have correlation with hypertension include calorie intake, number of meals per day, lack of physical activity in the present study.